Down syndrome and DYRK1A overexpression: relationships and future therapeutic directions - Murphy, Aidan J.; Wilton, Steve D.; Aung-Htut, May T.; McIntosh, Craig S. (Frontiers in Molecular Neuroscience, 2024)
Down syndrome is a genetic-based disorder that results from the triplication of chromosome 21, leading to an overexpression of many triplicated genes, including the gene encoding Dual-Specificity Tyrosine Phosphorylation-Regulated Kinase 1A (DYRK1A). This protein has been observed to regulate numerous cellular processes, including cell proliferation, cell functioning, differentiation, and apoptosis. Consequently, an overexpression of DYRK1A has been reported to result in cognitive impairment, a key phenotype of individuals with Down syndrome. Therefore, downregulating DYRK1A has been explored as a potential therapeutic strategy for Down syndrome, with promising results observed from in vivo mouse models and human clinical trials that administered epigallocatechin gallate. Current DYRK1A inhibitors target the protein function directly, which tends to exhibit low specificity and selectivity, making them unfeasible for clinical or research purposes. On the other hand, antisense oligonucleotides (ASOs) offer a more selective therapeutic strategy to downregulate DYRK1A expression at the gene transcript level. Advances in ASO research have led to the discovery of numerous chemical modifications that increase ASO potency, specificity, and stability. Recently, several ASOs have been approved by the U.S. Food and Drug Administration to address neuromuscular and neurological conditions, laying the foundation for future ASO therapeutics. The limitations of ASOs, including their high production cost and difficulty delivering to target tissues can be overcome by further advances in ASO design. DYRK1A targeted ASOs could be a viable therapeutic approach to improve the quality of life for individuals with Down syndrome and their families.